Transformations in Schooling
VIII, 276 p.
Keywords: By the end of the Twentieth century, formal schooling - once the privilege of male elites - had become accessible to women, the working class and some ethnic minorities. The essays in this volume explore the historical origins of this transformation, analyzing struggles Australia, Canada, China, Columbia, India, the United States, and South Africa.